Per Vaginal Delivery of Foal through Fetotomy in a Mare with Fractured Pelvis - Sahil,; Kumar, Brijesh; Patel, Lalit; Kohl, Kalpendra; Chandra, Pradeep; Hitesh,; Yadav, Raman; Vandana,; Sahu, Tarun Kumar (The Indian Journal of Animal Reproduction, 2022)
Dystocia in the mare is a very challenging situation because of long extremities of fetus, strong contraction by dam creating problems in correction of maldispositions. Careful handling of dystocia and efficient post-obstetrical management is key to the survival of the mare and foal and subsequent fertility of the dam. The current report describes a rare case of dystocia that involved both fetal and maternal causes. The maternal cause was the obstruction of the birth canal by a callus along with acute deviation of head and neck to the left side and bilateral knee flexion at the level of the pelvic brim which was efficiently treated by percutaneous fetotomy and mutations.
Keywords: Pelvic fracture; Fetotomy; Mare dystocia; Lateral Deviation